Book review: Darlene J. Sadlier, The Portuguese-speaking Diaspora: Seven Centuries of Literature and the Arts Austin. Issue 2 (July 2021) - Sinha, Neha
Darlene J. Sadlier, The Portuguese-speaking Diaspora: Seven Centuries of Literature and the Arts Austin . University of Texas Press, 2016, pp. 314. Price US 90 (hard cover). ISBN 1477310541, 9781477310540.